Observation and estimation of photosynthetically active radiation in Lhasa (Tibetan Plateau). Issue 6 (15th March 2015) - Peng, Simao; Du, Qingyun; Lin, Aiwen; Hu, Bo; Xiao, Ke; Xi, Yuliang
Abstract In this study, we measured photosynthetically active radiation (PAR) and global solar radiation (G) in Lhasa, located on the Tibetan Plateau, from 2006 to 2012 to examine the PAR and PAR/G (PAR fraction) seasonal characteristics. The maximum and minimum values of both PAR and the PAR fraction occurred in summer and winter, respectively. Moreover, the PAR and PAR fraction annual averages were 38.64 mol m−2 d−1 and 1.84 mol M J−1, respectively. An efficient all-weather model used for estimating PAR under various sky conditions was developed based on the relationships among PAR, the cosine of the solar zenith angle and the clearness index in Lhasa. The model also produced acceptable estimations of PAR with high accuracy at the Donghu and Sanjiang weather stations. A PAR dataset was reconstructed from G using the newly developed model for the period 1961–2012. The modelled annual mean daily PAR was approximately 37.62 mol m−2 d−1. A significant decreasing trend (−0.61 mol m−2 per decade) over the last 50 years was observed on the Tibetan Plateau; this decrease was largest in autumn (−1.024 mol m−2 per decade), and relatively small decreases were observed in summer. The results also revealed that PAR began increasing at 0.164 mol m−2 per year from 1991 to 2012, which was inconsistent with the variations of G. The proposed all-weather PAR model could be useful for ecological modelling and agricultural processes in the Tibetan Plateau region of China.